The Hippo Pathway: A Master Regulatory Network Important in Cancer - Liu, Qiuping; Liu, Xiaomeng; Song, Guanbin (Cells (Basel, Switzerland), 2021)
The Hippo pathway is pervasively activated and has been well recognized to play critical roles in human cancer. The deregulation of Hippo signaling involved in cancer development, progression, and resistance to cancer treatment have been confirmed in several human cancers. Its biological significance and deregulation in cancer have drawn increasing interest in the past few years. A fundamental understanding of the complexity of the Hippo pathway in cancer is crucial for improving future clinical interventions and therapy for cancers. In this review, we try to clarify the complex regulation and function of the Hippo signaling network in cancer development, including its role in signal transduction, metabolic regulation, and tumor development, as well as tumor therapies targeting the Hippo pathway.